Peran Perempuan Dalam Upaya Peningkatan Ekonomi Di Dusun 1 Desa Paya Mabar - Putri Adila; Khairunnisah Khairunnisah; Muhammad Arif (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research employs qualitative approaches to investigate how women contribute to enhancing the family's financial situation within Islamic frameworks. It delves into the factors impacting their roles and examines their involvement in household duties, empowerment initiatives, and managing various responsibilities. The findings highlight that women primarily contribute to the family economy by engaging in daily household tasks, participating in empowerment programs, and managing their time across different roles. Additionally, their earnings are crucial in financially supporting the family's needs.